Diversity of Staphylococcus aureus enterotoxin genes and its potential impact on severity of mastitis in dairy cows - Dantas, Stéfani Thais Alves; Silva, Laura Beatriz Borim da; Takume, Laura Tiemi Suehiro; Rossi, Bruna Fernanda; Bonsaglia, Érika Carolina Romão; Fernandes Júnior, Ary; Pantoja, José Carlos de Figueiredo; Dos Santos, Marcos V; Gonçalves, Juliano L; Ribon, Andrea O B; Silva, Nathalia C C; Rall, Vera Lucia Mores (Elsevier, 2024)
Staphylococcus aureus enterotoxins (SEs) can lead to food poisoning and appear to play a pivotal role in the development and severity of mastitis. This study aimed to evaluate whether the presence and diversity of S. aureus Enterotoxin genes mastitis-causing are associated with the development and severity of mastitis in dairy cows. Comparative analysis of S. aureus isolates from cows with clinical and subclinical mastitis (103 isolates each, CM and SM respectively) was conducted, examining the occurrence of enterotoxins (sea-see, seg-sez, sel26, sel27, sel01 and se02). Clinical isolates exhibited greater diversity, with 14 genes compared to four in subclinical isolates, and higher gene frequency (100 % vs. 86.4 %). Among the classical SEs, only sec (1 %) and sed (4.9 %) were detected in clinical isolates, suggesting a potential insignificance in the development of mastitis. Conversely, the selw and selx genes were among the most prevalent in both clinical and subclinical mastitis isolates. While their role in human food poisoning has not been definitively established, they appear to influence mastitis development. Statistical analysis revealed significant differences in clinical isolates carrying seg, seh, sei, seo, seul1, seul2, selw, and selx genes compared to subclinical isolates, suggesting their potential involvement in the severity of mastitis. Determining the frequency of SE gene and its role in mastitis establishment and in clinical mastitis severity, as well as understanding how enterotoxins contribute to pathogenicity in clinical and subclinical mastitis, is crucial for guiding optimal medical therapy for animals and establishing effective veterinary treatments to mitigate economic losses in the dairy industry.